2021
DOI: 10.1210/endocr/bqab068
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression ofTakifugu rubripesGonads During AI- or MT-induced Masculinization and E2-induced Feminization

Abstract: Elucidating the global molecular changes that occur during aromatase inhibitor (AI)- or 17α-methyltestosterone (MT)-induced masculinization and estrodiol-17β (E2)-induced feminization is critical to understanding the roles that endocrine and genetic factors play in regulating the process of sex differentiation in fish. Here, fugu larvae were treated with AI (letrozole), MT, or E2 from 25 to 80 days after hatching (dah), and gonadal transcriptomic analysis at 80 dah was performed. The expression of dmrt1, gsdf,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…Figure 1 shows the results of the histological analysis of the gonads. As reported by Yan et al, sex reversed larvae were not observed in the control groups [ 22 ]. Gonads from the C-XX group occupied the ovarian cavities, which were filled with a small number of oocytes and a large number of oogonia, closely arranged on the oviposition plate.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…Figure 1 shows the results of the histological analysis of the gonads. As reported by Yan et al, sex reversed larvae were not observed in the control groups [ 22 ]. Gonads from the C-XX group occupied the ovarian cavities, which were filled with a small number of oocytes and a large number of oogonia, closely arranged on the oviposition plate.…”
Section: Resultsmentioning
confidence: 59%
“…In T. rubripes , previous studies have also found that treatment with E 2 , during early sex differentiation, can induce feminization [ 8 , 48 , 49 ]. In our previous study, by E 2 -treatment (100 μg/L/time, 2 h/time, 1 time/day, from 25 dah to 55 dah), feminization of XY T. rubripes was induced, and the results of the transcriptomic analysis of gonads showed that a large number of DEGs and pathways involved in the process of feminization of XY T. rubripes [ 22 ]. For example, the expression of cyp19a1a , foxl2 , gsdf , dmrt1 , cyp11a1 , cyp17a1 , hsd3b1 , hsd17b1 and cyp11c1 changed dramatically in the gonad when torafugu were treated with E 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations